2019
DOI: 10.1097/scs.0000000000005142
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Computed Tomography Analysis of Stability Following Two- and Three-Point Fixation With Biodegradable Plates Among Patients With Zygomatic Fracture

Abstract: Background: Open reduction followed by internal fixation has been regarded as the most effective technique for the surgical repair of zygomatic fractures. However, the ideal number and locations of internal fixation points to maintain stable reduction remain controversial. Using 3-dimensional computed tomography, we aimed to compare the stability of 2-point and 3-point fixation among patients who had undergone surgical repair of zygomatic bone fractures. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…A estabilidade da fixação de pontos, sendo de 2 e 3 pontos utilizando somente materiais reabsorvíveis definiu que a fixação de 2 pontos do zigoma com materiais biodegradáveis é tão estável quanto a fixação de 3 pontos 22,24 , corroborando com os estudos de Ueki et al 25 , e Song et al 23 , onde revelaram que uma fixação híbrida de placas e parafusos absorvíveis pode ser útil e confiável em cirurgias ortognáticas e na diminuição de fraturas póscirúrgicas de corpo de mandíbula, respectivamente.…”
Section: Discussionunclassified
“…A estabilidade da fixação de pontos, sendo de 2 e 3 pontos utilizando somente materiais reabsorvíveis definiu que a fixação de 2 pontos do zigoma com materiais biodegradáveis é tão estável quanto a fixação de 3 pontos 22,24 , corroborando com os estudos de Ueki et al 25 , e Song et al 23 , onde revelaram que uma fixação híbrida de placas e parafusos absorvíveis pode ser útil e confiável em cirurgias ortognáticas e na diminuição de fraturas póscirúrgicas de corpo de mandíbula, respectivamente.…”
Section: Discussionunclassified
“…22 Na and Lim et al had found no difference in stability between two point and three point fixation however he found difference in the facial projection. 23 Wail et al compared two and three point fixation in two groups and evaluated surgical outcomes with CT scans. He found no significant difference in stability and concluded that two-point fixation is as good as three-point fixation with respect to stability of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In the 2-point fixation model, FZ fixation is indispensable based on a report pointing out that this site is the most critical region for fixation of ZMC fracture. 3,25 In a mechanical test, strength usually indicates a load value, which, when applied, causes the specimen to reach the fracture or yield point. On the other hand, stiffness is a property that resists deformation when an external force is applied to the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Our ZMC fractured model was fixed using 2- and 3-points. In the 2-point fixation model, FZ fixation is indispensable based on a report pointing out that this site is the most critical region for fixation of ZMC fracture 3,25 …”
Section: Discussionmentioning
confidence: 99%